Longitudinal study of prevalence and spatio‐temporal distribution of Borrelia burgdorferi sensu lato in ticks from three defined habitats in Latvia, 1999–2010. (14th July 2020) - Okeyo, Mercy; Hepner, Sabrina; Rollins, Robert E.; Hartberger, Christina; Straubinger, Reinhard K.; Marosevic, Durdica; Bannister, Stephanie A.; Bormane, Antra; Donaghy, Michael; Sing, Andreas; Fingerle, Volker; Margos, Gabriele
Summary: Members of the Borrelia burgdorferi sensu lato (s.l.) species complex are known to cause human Lyme borreliosis. Because of longevity of some reservoir hosts and the Ixodes tick vectors' life cycle, long‐term studies are required to better understand species and population dynamics of these bacteria in their natural habitats. Ticks were collected between 1999 and 2010 in three ecologically different habitats in Latvia. We used multilocus sequence typing utilizing eight chromosomally located housekeeping genes to obtain information about species and population fluctuations and/or stability of B. burgdorferi s.l. in these habitats. The average prevalence over all years was 18.9%. From initial high‐infection prevalences of 25.5%, 33.1% and 31.8%, from 2002 onwards the infection rates steadily decreased to 7.3%. Borrelia afzelii and Borrelia garinii were the most commonly found genospecies but striking local differences were obvious. In one habitat, a significant shift from rodent‐associated to bird‐associated Borrelia species was noted whilst in the other habitats, Borrelia species composition was relatively stable over time. Sequence types (STs) showed a random spatial and temporal distribution. These results demonstrated that there are temporal regional changes and extrapolations from one habitat to the next are not possible.